Host-Guest Expectations of Service Quality at Small Island Settings: A Cross-Cultural Approach - Ismail, Fathilah; Puad Mat Som, Ahmad; Falindah Padlee, Siti; Mariam Wan Abdullah, Wan (International Journal of Engineering and Technology, 2018)
One of the important issues for sustainable island tourism is knowledge about the needs of the host and tourist. As tourism is now becoming a global issue, there is also a need to examine this issue from the context of a cross-culture. A better understanding of cultural dissimilarities between hosts and guests at certain areas of destinations could improve tailored services and increase satisfaction for both the host and tourists. Existing studies related to expectation mainly undertaken from the tourist view. However, this study takes into consideration the expectation of service quality from touristsâ€™ perspectives as well as host community. This study aims to gain some understanding about the impacts of cross-cultural dissimilarities between hosts and tourists by measuring their mutual expectations. Survey data is collected from Perhentian and Redang Islands, Malaysia. Two sample groups were involved in the study: host and tourists (Malay, Chinese, English and European). This study adopted two methods - the Mann-Whitney U-test and the Principal Components Analysis (PCA). The findings of this study demonstrate that mutual expectations between hosts and guests diverge across the cultural groups.Â This study contributes to the existing literatures related to service quality and highlights the importance of cultural differences in providing better quality tourism services particularly to island tourists in Malaysia and elsewhere.Â .Â